GRAPHITE : The H to B of Contemporary Pencil Art & Drawings (Hong Kong : Viction:ary, 2022)
At a time when almost everything can be digitally done up to perfection, the smudges and smears by graphite can be refreshing to the eye and unapologetically human touching viewers to the core. As a creative tool, it can also be the simplest and most affordable medium with which to express oneself and find joy. Graphite is a stunning collection of pencil artwork by creatives around the world who have skilfully mastered the art of drawing by hand to make their mark. In a twist, the book is arranged by grading scale with works progressing from H or hardness to B or blackness and through every gradation in between. Featuring various subject matters and styles, it makes for a beautiful addition to the bookshelf and invites you to step away from your screen every now and then to, perhaps, pick up a pencil yourself and appreciate the simple things in life.
Keywords: Pencil drawing; Illustrated works